Management, co-management, or no management? : major dilemmas in southern African freshwater fisheries - Jul-Larsen, Eyolf; Food and Agriculture Organization of the United Nations (Rome : Food and Agriculture Organization of the United Nations, 2003)
Vol. 1 synthesizes the findings of ten case studies published in v. 2. The case studies have been conducted in five medium-sized lakes in t he Democratic Republic of the Congo, Malawi, Zambia and Zimbabwe. The s ynthesis focuses on three features relevant for the SADC region: How ha s fishing effort developed in these lakes over the last 50 years? What causes changes in fishing effort? How do fishing effort and environment al factors compare in their effects on the regeneration of fish stocks?
[v.] 1. Synthesis report -- [v.] 2. Case studies.
Includes bibliographical references.
Keywords: Fisheries -- Africa, Southern